Bibliometric Analysis: Parenting Program During the Worldwide Covid-19 Pandemic - Nirwana, Evi Selva; Rachmat, Irfan Fauzi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Childcare programmes have been the subject of extensive research. However, research mapping on parenting programmes during the Covid-19 pandemic is still very scarce. Therefore, the purpose of this bibliometric analysis is to compile an overview of childcare research during the Covid-19 pandemic. In this study, a total of 200 articles were collected from the Scopus database related to the theme